2021
DOI: 10.1093/advances/nmab057
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Patterns and Pregnancy Hypertension in Low- and Middle-Income Countries: A Systematic Review and Meta-analysis

Abstract: Healthy maternal diets can lower the odds of developing pre-eclampsia, a direct and second leading cause of maternal death, globally. However, there is a research gap in low- and middle-income countries (LMIC), which bear a disproportionate burden of these deaths. The objectives of this systematic review were to: 1) evaluate the association between dietary patterns in pregnancy and hypertensive disorders, including pre-eclampsia for pregnant and postpartum women in LMIC, and 2) compile barriers and facilitator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…The review consisted of four, large, HIC-based cohort studies: three from the Norwegian Mother and Child Cohort Study (MoBa) that assessed maternal diet in the second trimester (80)(81)(82) and the Generation R Cohort Study from the Netherland with assessment at a median 13.5 weeks (83). A subsequent meta-analysis of LMIC-based studies found that adequate (≥1-3 servings/week) vegetable consumption reduced the odds of developing pre-eclampsia by 62% (OR 0.38, 95% CI: 0.18 to 0.80, 4 studies, 1,391 participants, I 2 85%) and by 58% with adequate (≥1-3 servings/week) fruit consumption (OR 0.42, 95% CI: 0.24 to 0.71, 5 studies, 1,676 participants, I 2 79%) compared to women with low or no consumption (84). Conversely, maternal diets https://doi.org/10.1017/S0007114522003889 Published online by Cambridge University Press characterized by ultra-processed foods was associated with higher odds of developing preeclampsia, based on high quality evidence and no heterogeneity between study results (56).…”
Section: Possible Associationsmentioning
confidence: 99%
“…The review consisted of four, large, HIC-based cohort studies: three from the Norwegian Mother and Child Cohort Study (MoBa) that assessed maternal diet in the second trimester (80)(81)(82) and the Generation R Cohort Study from the Netherland with assessment at a median 13.5 weeks (83). A subsequent meta-analysis of LMIC-based studies found that adequate (≥1-3 servings/week) vegetable consumption reduced the odds of developing pre-eclampsia by 62% (OR 0.38, 95% CI: 0.18 to 0.80, 4 studies, 1,391 participants, I 2 85%) and by 58% with adequate (≥1-3 servings/week) fruit consumption (OR 0.42, 95% CI: 0.24 to 0.71, 5 studies, 1,676 participants, I 2 79%) compared to women with low or no consumption (84). Conversely, maternal diets https://doi.org/10.1017/S0007114522003889 Published online by Cambridge University Press characterized by ultra-processed foods was associated with higher odds of developing preeclampsia, based on high quality evidence and no heterogeneity between study results (56).…”
Section: Possible Associationsmentioning
confidence: 99%
“…With the exception of calcium, where decades of intervention trials corroborate with early epidemiological observations and understandings of biological mechanisms on evidence of a protective effect against preeclampsia, many potential maternal dietary factors are not supported by results of supplementation trials [124]. For example, though maternal serum vitamin C [52], zinc [58] and iron [67] have strong associations with the development of pre-eclampsia and make biological sense, supplementation resulted in non-significant effects [124][125][126][127]. Findings from this scoping review may help to shed light on the discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…As more evidence supports the positive benefits of healthy diet, such as lower risk of preeclampsia with DASH and higher vegetable and fruit consumption, this messaging needs to be disseminated. 31 …”
Section: Discussionmentioning
confidence: 99%